Routes and relations in Scandinavian interfaith forums: Governance of religious diversity by states and majority churches - Paulsen Galal, Lise (Social compass, 2018)
In the Scandinavian countries of Denmark, Norway, and Sweden, as elsewhere in Europe, governance of religious diversity has become a matter of renewed concern. A unique aspect of the Scandinavian situation is the hegemonic status of the respective Lutheran Protestant majority churches, usually referred to as folk churches', with which the majority of the population associates, alongside a prevalence of high degrees of regional secularism. As such, the majority churches have played a key role as both instigators and organisers of several interfaith initiatives, and have thereby come to interact with the public sphere as providers of diversity governance. Based on country-level studies of policy documents on majority-church/interreligious relations and field studies, this article sets out to explore the prompting and configuration of majority-church-related interfaith initiatives concerning church-state relations and the governance of religious diversity.